Interpreters Training and the note-taking skill for consecutive interpreting: Reflexiones sobre la preparación profesional del intérprete - Usquiano Piscoya, María Magdalena; Torres Vargas, Esdras Joel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper is focused on the development of the note-taking skill in a group of interpreters in training, considering that this technique is an important and supportive resource for a speech transmitted in a different language to be reformulated with precision and order. In the theoretical framework, the interpretation process, the consecutive modality and the foundations of the annotation are examined. This research is based on the analysis of apprentices’ academic training in relation to the aptitudes and abilities required in this profession with the aim of facilitating the achievement of an optimal professional profile that ensures an adequate performance and a successful insertion in the labour market.